Identification of novel PPARγ agonist from GC-MS analysis of ethanolic extract of Cayratia trifolia (L.): a computational molecular simulation studies - Palanisamy CHELLA PERUMAL, Sundaram SOWMYA, Prabhakaran PRATIBHA, Balasubramanian VIDYA, Palanirajan ANUSOORIYA, Thangarajan STARLIN, Ramasamy VASANTH, D. JEYA SUNDRA SHARMILA, Velliyur Kanniappan GOPALAKRISHNAN (Journal of Applied Pharmaceutical Science, 2014)
Peroxisome Proliferator-Activated Receptor gamma (PPARγ) is a nuclear receptor family transcription factor that is expressed in several types of cancers. Antiproliferative and proapoptotic actions of PPARγ agonists suggesting that, it could be a promising therapeutic target for the treatment of variety of cancers. Therefore, the main aim of this study is attempt to identify the novel PPARγ agonist from presence of bioactive compounds in ethanolic extract of Cayratia trifolia using GC-MS analysis and Computational molecular simulation studies. The GC-MS analysis revealed that the ethanolic extract of Cayratia trifolia (L.) (whole plant) consist of 20 bioactive compounds which embrace many biological activities against variety of diseases. Molecular docking studies (Glide 5.5 from Schrödinger suite) exposed that, out of 20 bioactive compounds, Cyclopentadecane, 9-Borabicyclo [3.3.1]nonane, 9-(2-propen-1-yloxy)-.1, 4,8,12,16-Tetramethylheptadecan-4- olide, Oxirane and Vitamin E shows the better glide score. ADME properties (QikProp 2.3 from Schrödinger suite) of these bioactive compounds were under the acceptable range. Based on the result it can be concluded that, these bioactive compounds may act as a good agonist for PPARγ. In future it may focus on current discoveries in PPARγ activation and possible anticancer therapeutic option.
Keywords: PPAR&gamma; , Cayratia trifolia (L.), GC-MS analysis, Molecular docking, ADME properties, PPAR&gamma; agonist.